Exploring Ethnomathematics In Saint Joseph Catholic Church, Jember - Anlika, Fabiana Triska; Marsidi, Marsidi; Panglipur, Indah Rahayu (Department of Mathematics Education, Faculty of Teacher Training and Education, Wisnuwardhana University of Malang, 2025)
Mathematics is often perceived as an abstract science detached from daily life, whereas in reality, it grows and develops within the culture of society. The ethnomathematics approach seeks to reveal how mathematical concept, especially geometry, manifest within cultural practices and architectural works. This study aims to explore the application of geometric concepts in the architecture of Saint Joseph Catholic Church Jember as an integration of mathematics, culture, and spirituality. The research employed a qualitative approach with an ethnographic case study design through participatory observation, interviews, and visual documentation. The result show that various elements of the church building, such as the bell tower, triangular roof, arched windows, pillars, stained glass, and floor mosaics, contain geometric concepts such as plane figures, solid figures, symmetry, similarity, and geometric transformations including reflection, rotation, and translation. Each architectural element demonstrates not only mathematical order but also symbolic meanings such as balance, perfection, and eternity that reflect Catholic faith values. The findings affirm that ethnomathematics serves as a bridge between science, art, and cultural values, making mathematics learning more contextual, meaningful, and grounded in real life.